1987
DOI: 10.2214/ajr.148.1.51
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the prostate gland: normal anatomy

Abstract: MR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(65 citation statements)
references
References 13 publications
2
58
0
3
Order By: Relevance
“…Hosseinzadeh and Schwarz have reported that susceptibility artifacts from air insufflation during EPI did not degrade the diagnostic quality of the ADC maps, with no geometric distortion (16). PZ was identified on T 2 -weighted axial images as a hyperintense area, while the CG had low signal intensity (20). In controls (group I), the ADC for PZ was 1.68 AE 0.…”
Section: Resultsmentioning
confidence: 95%
“…Hosseinzadeh and Schwarz have reported that susceptibility artifacts from air insufflation during EPI did not degrade the diagnostic quality of the ADC maps, with no geometric distortion (16). PZ was identified on T 2 -weighted axial images as a hyperintense area, while the CG had low signal intensity (20). In controls (group I), the ADC for PZ was 1.68 AE 0.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, MRI allows more accurate differentiation and segmentation of the transition zone and peripheral zone (18)(19)(20)(21). Our group had validated total prostate volume derived from image segmentation of prostate images obtained on a 3.0 T MRI with the weights of human radical prostatectomy specimens (22).…”
Section: Role Of Prostatic Volume Determination In Bph Managementmentioning
confidence: 99%
“…2 and 7). The puborectalis muscle may appear asymmetric in thickness on either side of the rectum because of chemical shift artifact occuring at the junction between muscle and fat [10] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%